Behavioral, physiological and genetic responses of the Yesso scallop Mizuhopecten yessoensis to the predation of sea star - Li, Xuetao; Li, Xian; Li, Danyang; Zhang, Dandan; Zhai, Xingyue; Wang, Xubo; Mao, Junxia; Tian, Ying; Liu, Ming; Chang, Yaqing; Hao, Zhenlin (Frontiers in Marine Science, 2025)
Predation is a major source of mortality in bottom - cultured scallops. To investigate the behavioral, physiological, and molecular mechanisms underlying predator - induced stress responses, an integrative approach was employed on Yesso scallops (Mizuhopecten yessoensis) exposed to the northern Pacific sea star (Asterias amurensis) by combining shell clap behavior quantification, enzyme activity assays, and transcriptomic analysis. Shell clap behavior, recorded using a force gauge system, revealed significantly increased contraction force and frequency following predator exposure, particularly in small and medium-sized scallops. Enzyme assays indicated significant changes in superoxide dismutase (SOD), catalase (CAT), arginine kinase (AK), and octopine dehydrogenase (ODH) across different tissues and size groups, with the most pronounced responses observed in medium - sized individuals. Transcriptomic profiling of adductor muscle in this group identified 514 differentially expressed genes (DEGs), of which 20 remained significant after P - value correction. These included genes such as paramyosin, myosin heavy chain, and Krüppel - like factors, involved in muscle structure, oxidative stress response, and amino acid metabolism. GO and KEGG enrichment analyses revealed significant metabolic shifts associated with oxidative stress and energy regulation. These findings demonstrate coordinated behavioral and molecular adaptations to predator stress in M. yessoensis and provide a foundation for improving predator management and selective breeding strategies in scallop aquaculture.